Community based lifestyle intervention for blood pressure reduction in children and young adults in developing country: cluster randomised controlled trial. (7th June 2010) - Jafar, Tazeen H; Islam, Muhammad; Hatcher, Juanita; Hashmi, Shiraz; Bux, Rasool; Khan, Ayesha; Poulter, Neil; Badruddin, Salma; Chaturvedi, Nish; ,
Abstract : Objective To assess the effectiveness of a community based lifestyle intervention on blood pressure in children and young adults in a developing country setting. Design Cluster randomised controlled trial. Setting 12 randomly selected geographical census based clusters in Karachi, Pakistan. Participants 4023 people aged 5-39 years. Intervention Three monthly family based home health education delivered by lay health workers. Main outcome measure Change in blood pressure from randomisation to end of follow-up at 2 years. Results Analysed using the intention to treat principle, the change in systolic blood pressure (adjusted for age, sex, and baseline blood pressure) was significant; it increased by 1.5 (95% confidence interval 1.1 to 1.9) mm Hg in the control group and by 0.1 (−0.3 to 0.5) mm Hg in the home health education group (P for difference between groups=0.02). Findings for diastolic blood pressure were similar; the change was 1.5 mm Hg greater in the control group than in the intervention group (P=0.002). Conclusions Simple, family based home health education delivered by trained lay health workers significantly ameliorated the usual increase in blood pressure with age in children and young adults in the general population of Pakistan, a low income developing country. This strategy is potentially feasible for up-scaling within the existing healthcare systems of Indo-Asia. Trial registration Clinical trials NCT00327574 .